A NEW SLOWFLARE STAR IN ORION - PARSAMIAN, E; HARO, G (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1969)
Photometric and spectroscopic characteristics are defined of the "slow" and "fast" flare stars. A new case of a "slow" flare star in Orion, is presented. It showed an increase of > 8.4 magnitudes in UV, during a period of 118 minutes. The peculiar physica
BOL OBS TONAN TACUB
Keywords: NEW, SLOWFLARE, STAR, ORION; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS